ANALISIS POTENSI EKOWISATA DAN RESPON MASYARAKAT DESA PENINJOAN KECAMATAN TEMBUKU KABUPATEN BANGLI - I Komang Agus Sugiarta; I Gst. Agung Oka Mahagangga (JURNAL DESTINASI PARIWISATA, 2016)
The village is located in the district peninjoan Tembuku Bangli regency. Peninjoan village has an area of ??1,350 hectares and has four village boundary that is north of the yangapi village, south Undisan village, Bangbang villages east and west Yangapi. The total number of villages included in the part of the six districts, namely Tembuku village including the village Jahem. Subdistrict Tembuku which has an area of ??4982 hectares with a population of 2007 to 2011 amounted to 34.040 inhabitants. Peninjoan village administratively divided in 13 hamlets.Peninjoan village ecotourism has the potential to be developed into a tourist attraction nature. Type of data and data sources used are qualitative, quantitative, primary and secondary data. Data collection techniques used were observation, interviews, questionnaires, documentary studies, literature study and data analysis techniques using qualitative descriptive analysis and SWOT analysis. Potential of the village peninjoan form unspoiled natural potential that can be developed into a tourist attraction. Natural potentials, which later will be made into eco-tourism agro-based activities in which these activities will be created an attraction that will be an attraction for tourists. The attraction in the form of tracking tours, cycling tour, and travel mute (silent tourism). To be able develop this potential requires the construction of facilities and infrastructure to support such activities.